Por favor me Ajudeem
Anexos:
![](https://pt-static.z-dn.net/files/d6d/32e665f78bdaadec0580539a6df4c860.jpg)
Soluções para a tarefa
Respondido por
1
Você so precisa inverter as frações, assim os expoentes ficam positivos.
![(\frac{2}{3})^{-1}= \frac{3}{2} (\frac{2}{3})^{-1}= \frac{3}{2}](https://tex.z-dn.net/?f=+%28%5Cfrac%7B2%7D%7B3%7D%29%5E%7B-1%7D%3D+%5Cfrac%7B3%7D%7B2%7D++)
![( \frac{1}{2})^{-3}= (\frac{2}{1})^3= 2^{3}=8 ( \frac{1}{2})^{-3}= (\frac{2}{1})^3= 2^{3}=8](https://tex.z-dn.net/?f=+%28+%5Cfrac%7B1%7D%7B2%7D%29%5E%7B-3%7D%3D+%28%5Cfrac%7B2%7D%7B1%7D%29%5E3%3D+2%5E%7B3%7D%3D8+++)
![( \frac{5}{2} )^{-2}= (\frac{2}{5})^2= \frac{4}{25} ( \frac{5}{2} )^{-2}= (\frac{2}{5})^2= \frac{4}{25}](https://tex.z-dn.net/?f=+%28+%5Cfrac%7B5%7D%7B2%7D+%29%5E%7B-2%7D%3D+%28%5Cfrac%7B2%7D%7B5%7D%29%5E2%3D+%5Cfrac%7B4%7D%7B25%7D++)
![( \frac{-7}{4} )^{-2}= (-\frac{4}{7})^2= \frac{16}{49} ( \frac{-7}{4} )^{-2}= (-\frac{4}{7})^2= \frac{16}{49}](https://tex.z-dn.net/?f=+%28+%5Cfrac%7B-7%7D%7B4%7D+%29%5E%7B-2%7D%3D+%28-%5Cfrac%7B4%7D%7B7%7D%29%5E2%3D+%5Cfrac%7B16%7D%7B49%7D+++)
Perguntas interessantes
Biologia,
11 meses atrás
Matemática,
11 meses atrás
ENEM,
11 meses atrás
Português,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Artes,
1 ano atrás